Malignant Salivary Gland Neoplasm - clinicopathological Study - Islam, Mohammed Shafiqul; Islam, Md Azharul; Sattar, Md Abdus; Ekramuddula, AFM; Hadi, Hossain Imam Al (Bangladesh Journal of Otorhinolaryngology, 2009)
Salivary gland neoplasm constitute about 10% of all head & neck neoplasm which represent 3% of all neoplasm of the body. In this study 50 patients of salivary gland neoplasm were studied to observe the frequency & clinicopathological pattern. Among 50 cases, 39(78%) were parotid neoplasm, 4 (8%) were submandibular neoplasm and 7 (14%) were minor salivary gland neoplasms. Among the parotid neoplasms, 13 (33.33%) were malignant neoplasms. Whereas in the submandibular neoplasm 2 (50%) were malignant neoplasms and for minor salivary glands tumour 4 (57.14%) were malignant neoplasms. Forty nine cases undergone some form of surgery. Most of them were treated by superficial or total conservative parotidectomy or radical parotidectomy/ submandibular gland excision with or without block dissection. Key word: Salivary gland neoplasm, Adenoid cystic carcinoma, Facial nerve. DOI: 10.3329/bjo.v14i1.3272 Bangladesh J of Otorhinolaryngology 2008; 14(1) : 1-5